1995
DOI: 10.1002/bjs.1800820640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct vision and electronic two- and three-dimensional display systems on surgical task efficiency in endoscopic surgery

Abstract: Task efficiency and knot strength was evaluated under standardized conditions using direct vision and electronic imaging with two-dimensional (2-D) and three-dimensional (3-D) systems. Three operators with different endoscopic surgical experience tied a surgeon's knot with standard endoscopic instruments using the three different visual systems in random order. Each operator tied 20 knots with each visual system. Median task efficiency (defined as the time to complete the knot) was 35.0 (interquartile range (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 2 publications
0
48
0
2
Order By: Relevance
“…However, the surgical literature shows contradictory results about the benefits of the 3D vision in laparoscopic surgery : some studies showing best motor performances with 3D vision (6-10) while others failed to obtain difference of performance between 2D and 3D (11)(12)(13). Divergence in all these results is partially because first-generation 3D systems, with their lower resolution, were compared with standard 2D systems (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the surgical literature shows contradictory results about the benefits of the 3D vision in laparoscopic surgery : some studies showing best motor performances with 3D vision (6-10) while others failed to obtain difference of performance between 2D and 3D (11)(12)(13). Divergence in all these results is partially because first-generation 3D systems, with their lower resolution, were compared with standard 2D systems (4).…”
Section: Introductionmentioning
confidence: 99%
“…In laparoscopic surgery, new systems allow the use of two-(2D) or three-dimensional (3D) vision. However, the literature reports contradictory results concerning the benefits of 3D vision: some studies show that better motor performances are obtained with 3D vision [1,8,19,25,26] while others fail to reveal any difference in performance between 2D and 3D vision [5,6,12,20]. In some studies [5], only complex tasks were performed faster and more easily with a 3D view whereas no difference between the use of 2D and 3D views appeared when performing the easiest tasks.…”
mentioning
confidence: 99%
“…For example, it would seem that stereoscopic endoscopes and displays would be more effective than monoscopic systems. Despite some positive performance data from commercial stereo systems [62], several research groups have shown them to provide little performance benefit [7], [63], [64], and their greater expense and complexity have prevented their adoption by surgeons. Improving viewing geometry by proper placement of the video monitor in the operating room may provide a solution as effective as these systems.…”
Section: B Systems Aspectsmentioning
confidence: 99%